Online Candidate Registration database educational study potential – desk research analytical method - Nalaskowski, Filip; Dejna, Dagna (Kultura-Społeczeństwo-Edukacja, 2020)
The text presents and describes the desk research analytical method. As an example of the practical application of the described method and a little-known data source, a short analysis of the database of Online Registration of andidates is presented. The components of the base are presented step by step, along with its information potential. A separate part is the presentation of the possible potential of IRK for educational research – in this case 11 years of candidates for archaeological studies at the Nicolaus Copernicus University. Analysis of the candidates’ origin, study potential, determination to take a specific major, etc.